Unsung heroes Yo save flood victims - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 24 December 2021 - Two individuals named ‘Yo’ were heroes for the residents of Taman Sri Damai Aman when they managed to save Hanafi Muhamad Yusoff’s family who lives in a nearby village.